Petanque research trends and developments in the last decade: a systematic review - Nurhasan Nurhasan; Muchamad Arif Al Ardha; Nur Salsabila Rhesa Pandhadha Putra; Abdian Asgi Sukmana; Chung Bing Yang; Kukuh Pambuka Putra; Sauqi Sawa Bikalawan; Mohd Firdaus Adli Bakri; Andika Bayu Putro; Resfiana Irani (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study analyzed petanque research and development trends in the last decade. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) research method was applied in this study. The identification of past research documents used the keyword “petanque,” and 14,829 documents were obtained from five journal databases (Scopus, Pubmed, Crossref, OpenAlex, and Google Scholar). There were 1,291 articles selected that fit the inclusion criteria to be analyzed in bibliometrics. Ten articles were selected for review based on the most citations and most relevant to the research topic. The research trend analysis shows a dynamic development and a significant increase. Visualization of bibliometric analysis shows a diverse keyword network but has not yet expanded into various fields. Based on the study results, petanque was developed as an achievement sport and socialized to the public to make it more attractive. Its correlation with sports injuries also needs to be developed because sports injuries are crucial in a sport. The literature review results presented discussions related to athlete performance from several aspects and organizational management. Developments in petanque sports research that move dynamically need to be extended from various aspects and fields to make it more complex and widespread.